Outcomes of intrahospital antimicrobial stewardship programs related to prevention of Clostridium difficile infection outbreaks - Biljana Mijović; Milena Dubravac-Tanasković; Maja Račić; Janja Bojanić; Slobodan Stanić; Dušica Banković Lazarević (Medicinski glasnik, 2018)
Aim: To synthesize evidence about the influence of individual antimicrobial stewardship programs (ASP) related to the prevention of Clostridium difficile (C. difficile) infection on primary and secondary outcomes. Methods: Relevant databases such as Medline, PUBMED, COCHRANE library and EBSCO were searched from 1 April to 27 April 2017. Additional studies were reached by the manual search for original articles in relevant journals. We included all randomized controlled, quasi-experimental and observational studies, published in the English language from 2007 onward, that evaluated effectiveness of ASP in preventing and controlling C. difficile associated disease (CDAD) among adult inpatients. Results: Implementation of ASP interventions was associated with CDAD incidence reduction in 62.5% studies, but no significant differences were reported for the duration of hospitalization, readmission and mortality rate. Improvements in prescribing patterns (decreased antimicrobial use or increased rational use) and microbial outcomes (decreased rates of selected antimicrobial-resistant bacteria) were reported. Evidence on the effects of ASP is mainly limited to the results of studies low in methodological quality with great heterogeneity of outcomes, interventions, and units in which CDAD incidence data were reported. Conclusion: Despite the low strength of evidence of reviewed studies, consistency of findings suggest the positive impact of antimicrobial stewardship programs on the prevention and control of nosocomial CDAD. The significance of this problem imposes randomized control trial use as the best instrument to provide highquality evidence. Further studies need to systematically analyse changes in all antibiotic use and its outcomes.
Keywords: Antimicrobial Stewardship Program; clostridium infections; disease outbreaks; prevention